Challenges experienced and resources identified by young to midlife couples 1–3 years post‐cancer diagnosis. Issue 1 (25th August 2021) - Lyons, Karen S.; Flatley, Christine; Gorman, Jessica R.; Hanan, Diana M.; Hayes‐Lattin, Brandon
Abstract: Objective: The purpose of this study was to explore what young to midlife couples viewed as their strengths as a couple and the greatest challenges in their experience with cancer 1–3 years post‐diagnosis. Methods: We used qualitative content analysis to extract common themes from open‐ended questions from 42 cancer survivors and their partners (aged 27–58). Patterns of themes by age and gender of the survivor were also explored. Results: Couples described both positive and negative impacts of the cancer experience: (1) strengthened the relationship, bringing couples closer together; (2) brought emotional strain to many areas of life, especially for partners; (3) created positive changes in lifestyle and new priorities for the couple; (4) created strain in the couple's relationship and intimacy; and (5) altered the role of family in supporting the couple. Couples also described four key strengths in dealing with the cancer experience: (1) drawing strength from shared love and mutuality; (2) communicating openly, even about the difficult stuff; (3) working together as a team to support each other; and (4) drawing strength from shared values and goals. Couples reported unmet needs related to the emotional and relational strain of the cancer experience, managing longer term survivor symptoms, fertility and physical intimacy, and lack of support or attention to the partner who often assumed the role of care partner. Conclusions: Themes are discussed in light of current dyadic concepts and importance of couple‐based interventions.